Pengaruh Model Cooperative Script terhadap Aktivitas dan Hasil Belajar Biologi Siswa Kelas VIII SMP Negeri 7 Lubuklinggau - Zico Fakhrur Rozi; Harmoko Harmoko; Ferty Lia Teresa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to see the effect of the Cooperative Script model on the activities and learning outcomes of biology students of class VIII of SMP Negeri 7 Lubuklinggau. Data collection techniques for learning outcomes use test techniques, while learning activity data use observation techniques. The average value of students for classes taught by Cooperative Script models is 70.11, while for classes taught using conventional learning is 64.22. The collected data were analyzed using t-test at a significant level α = 0.05 then obtained (2.45)> (1.67), there was an effect of the Cooperative Script model on biology learning outcomes of Grade VIII students of SMP Negeri 7 Lubuklinggau. The results of observations of the learning activities of the first meeting obtained an average value of 75.33% with enough categories and the results of observations of the learning activities of the second meetings obtained an average value of 75.94% with enough categories, which means biology learning activities for VIII grade students of SMP Negeri 7 Lubuklinggau is further improved after being treated using the Cooperative Script model. In conclusion, the cooperative script model has a statistically significant effect on increasing the activities and learning outcomes of biology students in grade VIII of SMP Negeri 7 Lubuklinggau. Keywords: learning activities, learning outcomes, cooperative script models